Analisis Tingkat Pemahaman Mahasiswa Terhadap Penulisan Karya Tulis Ilmiah Berbasis Pengalaman Di STIKes Binalita Sudama Medan - Harahap, Sri Wida; Kesya N. Lumbantobing; Berkat Panjaitan (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
This research entitled Writing scientific papers. The purpose of this study is to find the shortcomings and weaknesses that are mostly carried out by students in making written works (thesis). The method used in this research is exploration (excavation) of the aspects to be revealed and analyzed using the percentage formula. From the analysis that has been carried out, the level of errors found is related to all aspects of scientific work. The highest is in the aspect of using Indonesian, while in the aspect of quoting, low in the aspect of the conclusion section and writing of bibliography and very low in the aspect of report structure, consistency of format and content of the paper. Errors in the use of language are found in all types of writing and are included in the high category.